Three Essays on the Effects of Government Taxation and Incentive Policies on Consumers' New Vehicle Purchase Decisions - Azarafshar, Roshanak (Université d'Ottawa / University of Ottawa, 2018)
Chapter 1. This chapter aims to find the effects of financial point of sales incentives on the sales of electric vehicles across the Canadian provinces from September 2012 to December 2016. The findings of my study indicate that purchase incentives cause the sales of new electric vehicles to increase by 8 percent on average due to a $1000 increase in incentives. I find that 47% of electric vehicle sales across the rebating provinces (Ontario, Quebec, and British Columbia) are attributed to the purchase incentives. Results of my counter-factual simulations imply that the cost of eliminating one tonne of carbon emissions across the provinces that offer incentives over the years of my study is, on average, $216/tonne CO2. Chapter 2. In light of the rapid increase in Canadian gasoline prices from 2000 to 2010, this chapter focuses on the relationship between gasoline price and demand for vehicle fuel efficiency across the Canadian forward sortation areas (FSA) over this period. I find that consumers respond to variations in gasoline price when deciding the fuel efficiency of their new vehicle; increases in gasoline price result in shifts in demand for more fuel-efficient vehicles and therefore improve the average fuel efficiency of the new vehicle fleet. I find that the elasticity of fuel economy with respect to gasoline price for new vehicles sold across the Canadian forward sortation areas (FSA) from 2000 to 2010 is -0.06 to -0.16. Results of further analyses imply that consumer are more responsive to rising and constant gasoline prices than falling prices and that urban residents are slightly more responsive to variations in gasoline price compared to residents of suburb regions. Chapter 3. This chapter investigates the effect of the carbon tax policy implemented by the Canadian Province of British Columbia on households’ new vehicle purchase decisions. I dis-aggregate the effects of gasoline price into two effects: the carbon tax and carbon tax-exclusive gasoline price. These effects are both measured along the extensive margin of replacing a fuel inefficient vehicle with a fuel-efficient vehicle. The results indicate that there is a significant negative relationship between both effects and fuel efficiency substitutions. However, vehicle fuel economy is more sensitive to changes in the carbon tax than to equivalent changes in the carbon tax-exclusive gasoline price. I find that the elasticity of fleet fuel economy with respect to the carbon tax ranges from -0.22 to -0.26 whereas this elasticity changes between -0.1 and -0.15 with respect to gasoline price (net of the carbon tax). I obtain consistent results when estimating the effect of both factors on fleet fuel economy conditional on fleet composition, indicating that almost all vehicle segments respond more strongly to changes in the carbon tax component of gasoline price than other components. Results also imply that, among all segments, the fuel consumption of compact sport utility vehicles (SUVs), minivans, and luxury high-end cars respond the most to the carbon tax.
Keywords: Government incentives; Electric vehicles; Gasoline price; Vehicle fuel efficiency; Carbon tax